Uncommon Terpenoids from Salvia Species: Chemistry, Biosynthesis and Biological Activities - Salar Hafez Ghoran; Fatemeh Taktaz; Ali Akbar Mozafari; Murat Tunçtürk; Nazim Sekeroglu; Anake Kijjoa (Molecules, 2022)
The search for new bioactive compounds from plant sources has been and continues to be one of the most important fields of research in drug discovery. However, Natural Products research has continuously evolved, and more and more has gained a multidisciplinary character. Despite new developments of methodologies and concepts, one intriguing aspect still persists, i.e., different species belonging to the same genus can produce different secondary metabolites, whereas taxonomically different genera can produce the same compounds. The genus Salvia L. (Family Lamiaceae) comprises myriad distinct medicinal herbs used in traditional medicine worldwide that show different pharmacological activities due to the presence of a variety of interesting specialized metabolites, including mono-, sesqui-, di-, sester-, tri-, tetra-, and higher terpenoids as well as phenylpropanoids, phenolic acid derivatives, lignans, flavonoids, and alkaloids. We herein summarize the research progress on some uncommon terpenoids, isolated from members of the genus Salvia, which are well recognized for their potential pharmacological activities. This review also provides a current knowledge on the biosynthesis and occurrence of some interesting phytochemicals from Salvia species, viz. C23-terpenoids, sesterterpenoids (C25), dammarane triterpenoids (C30), and uncommon triterpenoids (C20+C10). The study was carried out by searching various scientific databases, including Elsevier, ACS publications, Taylor and Francis, Wiley Online Library, MDPI, Springer, Thieme, and ProQuest. Therefore, 106 uncommon terpenoids were identified and summarized. Some of these compounds possessed a variety of pharmacological properties, such as antibacterial, antiviral, antiparasitic, cytotoxic and tubulin tyrosine ligase inhibitory activities. Due to the lack of pharmacological information for the presented compounds gathered from previous studies, biological investigation of these compounds should be reinvestigated.